Kajian Biblika Makna Ibadah yang Murni dalam Yakobus 1:26-27 Dan Implikasinya Bagi Orang Percaya Masa Kini - Paulus Kunto Baskoro; Joseph Christ Santo (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2021)
Worship is an important part of the life of a believer. Worship cannot be replaced with anything in this life. Because worship is part of the lifestyle of every believer. When it comes to worship, it is immediately focused on the concept of praise, worship and listening to God’s Word in church buildings, retreats or commission services. This is not wrong; indeed, the essence of worship is to perform religious rituals to meet God. But there is something interesting in James 1:26-27 mention of true worship. In order to obtain accurate and accountable data, in this study authors used the method of writing descriptive literature. The purpose of this writing is Frist, to reveal and straighten out an incorrect understanding of a concept of worship according to the truth of God’s Word. Second, contribute to believers in thinking to be able to be role models in society. Third, it provides a nuance of the mindset of believers to reflect practical worship into a holistic form of service.